Radiating the prostate bed in relapsed oligometastatic prostate cancer: How comprehensive should we be?. Issue 5 (11th January 2022) - Cao, Yilin; Song, Daniel Y.; Deville, Curtiland; DeWeese, Theodore L.; Greco, Stephen; Tran, Phuoc T.; Deek, Matthew P.
Abstract: Purpose: A subset of patients with high‐risk pathological features at radical prostatectomy recur with oligometastatic disease. The aim of this study is to investigate the rate of prostate bed recurrence, with or without history of prostate bed irradiation (PBRT), in oligometastatic prostate cancer (OMPC) patients after metastasis‐directed therapy (MDT). Methods: We performed a retrospective analysis of hormone‐sensitive OMPC patients treated initially with curative‐intent radical prostatectomy followed by disease recurrence and metastasis‐directed stereotactic ablative radiotherapy (SABR) at our institution. Prostate bed recurrence rates were compared between patients who had PBRT at any point (i.e., before oligometastatic diagnosis or concurrently with MDT) versus those with no history of PBRT. Results: Seventy‐seven patients were included, and 68.8% had received PBRT. There were no significant differences in baseline characteristics between those who had received and had not received PBRT. There were five prostate bed recurrences following MDT, specifically with a 24‐month cumulative incidence of 30.4% in patients who did not have PBRT and 2.4% in those who did ( p = 0.03). Three of the five recurrences were isolated to the prostate bed at time of recurrence. Conclusions: Relapsed oligometastatic prostate cancer patients who have not received maximal local consolidative therapy to the prostate bed may have higher rates of local failure. Prospective studies are warranted investigating when prostate bed irradiation should be considered for patients after radical prostatectomy who ultimately have oligometastatic prostate cancer.